Herbal medicines for the treatment of otitis media with effusion: a systematic review of randomised controlled trials - Son, Mi Ju (BMJ Open, 2016)
OBJECTIVES: This systematic review aimed to assess the clinical evidence supporting the use of herbal medicines (HMs) for the treatment of otitis media with effusion (OME). DESIGN: Systematic review and meta-analysis. DATA SOURCES: MEDLINE, EMBASE, Cochrane Library, AMED, CINAHL and three trial registries were searched up to January 2015. We also searched five Korean medical databases (KoreaMed, RISS, OASIS, DBPIA and KISS) and three Chinese databases (CNKI, Wanfang and VIP). STUDY ELIGIBILITY CRITERIA: This study included randomised clinical trials that reported the effects of HM for OME. The primary outcome was the complete resolution of OME at 2 or 3 months post randomisation. Secondary outcomes included the partial or complete resolution at all possible time points and hearing test. Three authors independently screened the titles and abstracts, selected studies and extracted the data relating to trial quality, characteristics and results. RESULTS: A total of 2141 potentially relevant studies were identified, of which 17 randomised clinical trials met our inclusion criteria. Most were evaluated as having a high or unclear risk of bias. Tongqiao tablets, Tongqiao huoxue decoctions and Tsumura-Saireito were associated with a lower complete or partial resolution rate when compared with conventional medicines (CMs) (p=0.02, p=0.0001, and p=0.04, respectively), and similar outcomes were observed with Huanglong tonger pills, Erzhang decoctions and Shenling baizhu powder when combined with CM versus CM alone (p<0.00001, p=0.02, and p=0.05, respectively). Tongqiao huoxue decoction plus CM appeared to be more effective than CM in terms of improving the pure tone threshold levels (p=0.0007). Tsumura-Saireito was found to affect the proportion of patients with normalised tympanometry (p=0.03). CONCLUSIONS: Despite some indications of potential symptom improvement, the evidence regarding the effectiveness and efficacy of HMs for OME is of poor quality and therefore inconclusive. PROTOCOL REGISTRATION NUMBER: CRD42013005430.